Cultural Differences in The Content of Employees' Psychological Contract: A Qualitative Study Comparing Belgium and China. Issue 1 (1st June 2020) - Du, Jiahong; Vantilborgh, Tim
This study qualitatively explores differences in psychological contract (PC) content between Belgian and Chinese employees, while attempting to understand these differences from the perspective of cultural values. We build on theory concerning horizontal and vertical individualism/collectivism to interpret differences in PC content. 21 Chinese and 20 Belgian employees were interviewed, with results indicating that Belgian interviewees' PCs tend to be balanced with an emphasis on egalitarian interpersonal relationships, reflecting a horizontal collectivist culture. We propose that a "culture of compromise" forms a fitting description for Belgian interviewees' PCs. For Chinese interviewees, the PC was characterized by mixed contracts aligning with the ideology of 'Utilitarianistic Guanxi', which forms a Chinese philosophy that combines the pursuit of profit with objective goods, reflecting a culture of vertical collectivism.